An Impact of ZigBee Technology in Data Communication System - Dhanya. T (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
ZigBee is an IEEE 802.15.4 standard for information interchanges with business and purchaser gadgets. It is composed around low-control utilization permitting batteries to keep going forever. The ZigBee standard gives system, security, and application bolster administrations working on top of the IEEE 802.15.4 Medium Access Control (MAC) and Physical Layer (PHY) remote standard. It utilizes a suite of innovations to empower adaptable, self-arranging, self-mending systems that can oversee different information movement designs. ZigBee is an ease, low-control, remote lattice organizing standard. The ease permits the innovation to be broadly sent in remote control and observing applications, the low power-use permits longer an existence with little batteries, and the cross-section systems administration gives high dependability and bigger range.ZigBee has been created to take care of the developing demand for able remote systems administration between various low power. In industry ZigBee is being utilized for cutting-edge robotized assembling, with little transmitters in each gadget on the floor, taking into consideration correspondence between devices to a focal PC. This new level of communication allows finely-tuned remote observing and control.